Bat Biology, Genomes, and the Bat1K Project: To Generate Chromosome-Level Genomes for All Living Bat Species - Teeling, Emma C.; Vernes, Sonja C.; Davalos, Liliana M.; Ray, David M.; P. Gilbert, M.Thomas; Myers, Eugene; Faisal Ali, Anwarali Khan; Bat1K Consortium (Annual Reviews, 2018)
Bats are unique among mammals, possessing some of the rarest mammalian adaptations, including true self-powered flight, laryngeal echolocation, exceptional longevity, unique immunity, contracted genomes, and vocal learning. They provide key ecosystem services, pollinating tropical plants, dispersing seeds, and controlling insect pest populations, thus driving healthy ecosystems. They account for more than 20% of all living mammalian diversity, and their crown-group evolutionary history dates back to the Eocene.